Pengembangan E-Booklet pada Sub Materi Peranan Bakteri Kelas X SMA sebagai Media Pembelajaran - Sherly Febriani; Laili Fitri Yeni; Eko Sri Wahyuni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research development model is based on research and development by Borg & Gall with changes by Sugiyono (2019) which only focuses on five stages: potential and problems, data collection, product design, design validation, and design revision. The purpose of this research is to create and develop E-Booklets as learning media to be tested for validity and reliability, so they are feasible to use. Instrument validation was carried out by two validators using the Guttman scale. Media validation was carried out by five validators using four rating scales based on the Likert scale. Validation is done by filling out a closed questionnaire. Media E-Booklet validation to assess four elements: format, content, language, and practicality. The E-Booklet validation analysis used the Aiken's V method and the reliability test used ICC. The results of the ICC reliability of 0.933 and the validity of Aiken of 0.95 place it in a very good category. The results of the validation show that the E-Booklet on the sub-material of the role of bacteria for class X SMA is a good learning medium so it is suitable for use in learning.